Guinea : First Review of the Arrangement Under the Three-Year Extended Credit Facility, Financing Assurances Review, and Request for Modification and for Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Guinea. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
The Guinean economy is growing at a faster than anticipated pace on the back of buoyant mining activity. The growth momentum is expected to continue, with real growth at about 6 percent in 2018 and over the medium term. However, risks of instability are heightened by the current electoral cycle.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet